(untitled) (Texas Journal of Philology, Culture and History, 2026)
This article provides a theoretical and methodological analysis of the study of the material and spiritual culture of the early Saka tribes of the Aral Sea region-an integral and strategic component of the Eurasian steppe civilization-in world historiography. The research examines the decline of certain longstanding scientific paradigms regarding nomadic tribes, alongside the specific socio-economic adaptation, economic types, and social structure of Saka society. Based on the archaeological data from key regional sites such as Uygarak, Southern and Northern Tagisken, and Sakarchaga, the paper comparatively analyzes diverse scientific hypotheses concerning the genesis of the Sakas, their unique burial practices, and the origins of their visual arts. Furthermore, focusing on the Kuysay culture of the Sarykamysh region, it elucidates theoretical approaches regarding localized Saka groups and their cultural-technological interactions with southern sedentary agricultural oases